Anosmia and dysgeusia associated with COVID-19 infection among patients visiting a tertiary hospital at Kaski, Nepal - Sharma, Swasti; Bhandari, Aakash Mani; Acharya, Ushant; Shakya, Ambalika; Goudel, Bonu; Banstola, Laxman (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: A number of studies have shown that anosmia and dysgeusia present as symptoms of COVID-19. These symptoms can appear with sudden onset following COVID-19 infection. The objective of the study was to observe epidemiological and clinical profile of COVID-19 patients who had experienced anosmia and dysgeusia. Methods: A cross-sectional study was carried out in Ear, Nose and Throat outpatient department of Pokhara Academy of Health Sciences over a period of two months, from February 2022 to March 2022. Patients visiting the outpatient department were enquired about the COVID-19 infection status in the past and symptoms related to taste and smell impairment were asked about. Results: Out of total 198 patients, 141 (71%) had experienced impairment of taste and smell, either one or both, while the rest did not develop such features after testing positive for COVID-19 virus. Conclusions: Anosmia and dysgeusia were common features in COVID-19 infection.